Analysis of Factors Affecting Food Delivery Users in Jabodetabek - Marleene Ratu Fiorentina; Usep Suhud; Ika Febrilia (LPPM Universitas Negeri Jakarta, 2021)
This research aims to identify whether brand image, trust, perceived value, and customer satisfaction affect customer loyalty and repurchase intention in food delivery users in Jabodetabek. This study used the SEM analysis method with quantitative analysis. This study used non-probability sampling techniques, sampling techniques to collect data using questionnaire surveys. The type of nonprobability sampling technique chosen is purposive sampling, with the number of respondents as many as 200 people. This study used the exploratory factor analysis (EFA) method and confirmatory factor analysis (CFA) method. The results of this study showed that brand image has a positive and significant influence on customer satisfaction, perceived value has a positive and significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant influence on customer loyalty and customer satisfaction has a positive and significant effect on repurchase intention.